Analisis Sistem Drainase RSUD Dr. Soekardjo Kota Tasikmalaya - Tantoh, Michael; Ramadan, Anri Noor Annisa; Hendardi, Agi Rivi (Universitas Siliwangi, 2024)
In 2022, Dr. Soekardjo Regional General Hospital in Tasikmalaya faced a serious challenge with its drainage system. Due to heavy rain, a 50 cm water puddle on the first floor posed a threat to patient safety and disrupted hospital operations. This research aimed to evaluate the capacity and effectiveness of the drainage system, ensuring its ability to handle water flow and prevent flooding and flood risks during rainfall. The research methods included rainfall analysis, flow modeling, and existing flow analysis involving 47 drainage channels of various shapes in Dr. Soekardjo Regional General Hospital. The identification results showed an average channel length of 27.41 m, width of 0.5 m, and height of 0.24 m. The flow rate of Dr. Soekardjo Regional General Hospital was 0.261 m3/s, the Citanduy River tributary flow was 0.093 m3/s, and the total flow was 0.354 m3/s. The analysis indicated that the existing channels were unable to accommodate both flow rates, resulting in backwater. To address the drainage issue, improvements to the channels, addition of infiltration wells, and creation of biopore infiltration holes are planned. Additionally, an aquifer will be established as an additional water reservoir, and the Citanduy River channel will be widened to optimize flow. It is hoped that these measures will reduce the risk of waterlogging and flooding, ensuring patient safety during the rainy season.